Social Value Construction in the Labuhan Parangkusumo Tradition: A Study of Cultural Meaning and Its Implications for Local Wisdom-Based Social Studies Education - Andri Yunan Nugroho; Sukadari; Victor Novianto; Esti Setiawati; Yanuar Bagas Arwansyah (Lembaga Bale Literasi, 2026)
This study analyzes the construction of social values in the Labuhan Parangkusumo tradition, a royal ceremonial ritual (hajad dalem) of Keraton Ngayogyakarta Hadiningrat held annually on the 30th of Rajab at Parangkusumo Beach, Bantul Regency, Yogyakarta. The study aims to identify embedded social values, analyze the cultural meanings of ritual symbols, and formulate pedagogical implications for social studies education based on local wisdom. The research employs a qualitative approach with ethnographic design. Data were collected through participatory observation in January 2026, in-depth interviews with ritual custodians (juru kunci), royal servants (abdi dalem), cultural leaders, and document analysis. Data analysis utilized Miles and Huberman's interactive model, anchored theoretically in Geertz, Berger–Luckmann, Turner, and Durkheim. The study identified six social values: harmony, mutual cooperation-solidarity-responsibility, tolerance-pluralism, spirituality-religiosity, disaster mitigation-ecological awareness, and leadership legitimation. Harmony functions as the core value connecting the other five values. Value construction unfolds through dialectical stages: externalization, objectivation, and internalization. All six values correspond directly with the dimensions of Profil Pelajar Pancasila in the Merdeka Curriculum. Conclusively, Labuhan Parangkusumo constitutes a legitimate local epistemological system, serving as a meaningful foundation for character education, authentic multiculturalism, and ecological literacy in social studies education.